2003
DOI: 10.1097/00001756-200312190-00019
|View full text |Cite
|
Sign up to set email alerts
|

Orphanin FQ/nociceptin blocks methamphetamine place preference in rats

Abstract: Orphanin FQ/nociceptin (NOC) has been reported to regulate dopaminergic neurotransmission in rewarding pathway, and to suppress the development of conditioned place preference (CPP) induced by certain addictive drugs. In this study, we investigated the effect of NOC on CPP induced by repeated administration of methamphetamine (MAP) in rats. Repeated administration of MAP (1 mg/kg, i.p.) induced substantial CPP. MAP-induced CPP was completely suppressed by NOC (10 nmol, i.c.v.). Pretreatment with [Nphe1]nocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…These results are consistent with previous studies showing that exogenous N/OFQ administration suppresses the acquisition or expression of drug-induced CPP (Ciccocioppo et al, 1999(Ciccocioppo et al, , 2000Murphy et al, 1999;Kotlinska et al, 2003;Kuzmin et al, 2003;Zhao et al, 2003;Sakoori and Murphy, 2004).…”
Section: Role Of Endogenous N/ofq In Balancing Hedonic Statesupporting
confidence: 93%
“…These results are consistent with previous studies showing that exogenous N/OFQ administration suppresses the acquisition or expression of drug-induced CPP (Ciccocioppo et al, 1999(Ciccocioppo et al, , 2000Murphy et al, 1999;Kotlinska et al, 2003;Kuzmin et al, 2003;Zhao et al, 2003;Sakoori and Murphy, 2004).…”
Section: Role Of Endogenous N/ofq In Balancing Hedonic Statesupporting
confidence: 93%
“…2. NOP receptor agonists block contextual drug associations (i.e., CPP) of every drug tested, including morphine, cocaine, amphetamine, and alcohol (Ciccocioppo et al, 2000;Kotlinska et al, 2002Kotlinska et al, , 2003Zhao et al, 2003;Sakoori and Murphy, 2004). This is consistent with a NOP receptor agonist-induced decrease in extracellular dopamine in the NAc (Murphy et al, 1996;Vazquez-DeRose et al, 2013).…”
Section: Future Directions and New Toolsmentioning
confidence: 68%
“…Initial studies demonstrated that N/OFQ is neither rewarding nor aversive (Devine et al, 1996). In fact, intracerebroventricularly administered N/OFQ can block morphine CPP and CPP induced by cocaine, alcohol, and methamphetamine (Ciccocioppo et al, 2000;Kotlinska et al, 2002Kotlinska et al, , 2003Zhao et al, 2003;Sakoori and Murphy, 2004). N/OFQ also blocks self-administration of alcohol (Ciccocioppo et al, 2004).…”
Section: Biologic Actions Of Nociceptin Opioid Peptide Receptorsmentioning
confidence: 99%
“…]nociceptin-NH 2 (UFP-101), suggesting that the buprenorphine-induced reduction in alcohol consumption is caused by activation of NOP receptors (Ciccocioppo et al, 2007). An NOP-mediated reduction in CPP and self-administration of a variety of abused drugs by N/OFQ is already well documented (Murphy et al, 1999;Kotliń ska et al, 2002;Ciccocioppo et al, 2003;Zhao et al, 2003). Therefore, it is possible that increasing the NOP agonist efficacy in buprenorphine, or other opioid ligands, may produce an effective nonaddicting analgesic and may be more efficacious than buprenorphine for drug abuse pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…N/OFQ, through NOP-receptor activation, has been shown to have antiopiate properties in the brain (Meunier et al, 1995;Reinscheid et al, 1995) and is able to block the reward induced by morphine (Murphy et al, 1999), cocaine (Kotliń ska et al, 2002;Sakoori and Murphy, 2004), ethanol (Ciccocioppo et al, 1999;Kuzmin et al, 2003), and methamphetamine (Zhao et al, 2003). N/OFQ, when administered intracerebroventricularly, also has been shown to block development of tolerance to morphine (Lutfy et al, 2001).…”
Section: Introductionmentioning
confidence: 99%